Meningkatkan Skill Dribbling Bermain Sepak Bola Menggunakan Metode Drill pada Siswa Kelas 5 Sekolah Dasar - Aziiz, Qowiyyun; Muhlisin, Muhlisin; Listiyariny, Dian (PGSD Universitas Muria Kudus, 2024)
This study aims to improve soccer playing skills through the drill method.The research method used is classroom action research (CAR) which was implemented at Wuwur State Elementary School in the 2023/2024 Academic Year on 20 fifth grade students with details of 12 male students and 8 female students. The research was conducted every Wednesday, April 3, 10, and 17, 2024. The research was carried out in two cycles which included planning, implementation, observation and reflection. Data collection techniques were carried out using observation, interviews, and documentation. The data analysis technique used was a qualitative data analysis technique consisting of three stages of activity, namely (1) data reduction, (2) data presentation and drawing conclusions, and (3) data verification.The results of the study showed that there was an increase in dribbling skills in soccer games through the drill method in PJOK learning in fifth grade students of Wuwur State Elementary School. The learning results for cycle 1 showed that 20 students had experienced an increase from pre-cycle, where initially there were 5 children (25%) who met the KKM to 13 children (65%) who had met the KKM value. Meanwhile, those who still do not meet the KKM have gone from 15 children (75%) to 7 children (35%). The highest score was from 80 to 85, the lowest score was 50 to 55 and the class average was from 55.25 to 67. In cycle 2 the completion score was originally 13 children (65%) to 15 (75%) children, those who had not completed it decreased from the original 7 children (35%) to 5 children (25%). Meanwhile, the highest score was originally 85 to 90, the lowest score was from 55 to 60 and the class average was from 67 to 75.75